STRATEGI KOMUNIKASI PEMASARAN GUS & YUK DALAM MEMPROMOSIKAN SITUS PENINGGALAN KERAJAAN MAJAPAHIT (STUDI DI KECAMATAN TROWULAN, KABUPATEN MOJOKERTO) - Mardiatna, Pradana Tera; Hamim, Hamim; Pratiwi, Ni Made Ida (representamen, 2018)
This event will be based on research by the tourism industry is an important legacy wasowned by Mojokerto tourism industry history in particular who are in district of Trowulan to inform tothe public. Paguyuban Duta Wisata Gus and Yuk Mojokerto is the organization that constructed by theYouth Sports culture and tourism Mojokerto PAGUK (Paguyuban Gus and Yuk) this organizationmoving in the field of tourism which is the task of an Ambassador of Tourism is helping the Tourismsector to promote the tourism industry in order to increase tourist visits. The research on the focus onthe historical attractions of sub trowulan tourism Candi Brahu Temple Bajang Ratu, Temple of rats,Temple Name Mace, and the great Hall with an integrated Pemasran communication theory orcommonly known with Intergrated Marketing Communications (IMC). This study uses qualitativemethods because in this study describes the situation so as to find the results of prediction.Researchers found a few things from the integrated marketing communication is lacking most of thefunctions and tasks DISPORABUDPAR, Gus and Yuk Mojokerto and Ma nager.The cause of all Personal Communications is less effective, so that the destination must be maximizedbecause it has a great asset for attracting tourists and the potential is large, located in district ofTrowulan.